Academic entitlement, consumerism, and professional preference - Kelso, Shelby (My University, 2017)
The goal of the current study was to examine whether perception of professor accommodations and trait entitlement affected student ratings of a professor’s overall likability and perceived rigor. Participants were randomly assigned to read a syllabus ostensibly written by a non-likeable professor who adopted consumerist conforming and accommodating rules or by a likeable professor who did not adopt consumerist conforming and accommodating rules. Participants then evaluated the professor on likability and perceived rigor, and completed measures of academic, academic consumerist, and generalized entitlement. First, analyses replicated previous results indicating a relationship between generalized entitlement and academic entitlement. Additionally, academic entitlement was found to be highly related to academic consumerist entitlement. Second, results indicated that participants liked professors who were more consumerist conforming and accommodating even when the professor was ‘meaner’ and had a less likable demeanor. Lastly, it was found that academic entitlement was negatively correlated with how likable participants found professors to be, even after controlling for which condition participants were in. Implications of the findings are discussed with regard to how entitlement and consumerist attitudes might affect college education and faculty.
A Thesis Submitted in Partial Fulfillment of the Requirements For the Degree of Master of Science in Psychology Cognitive & Affective Science